Nerve growth factor promotes lysyl oxidase-dependent chondrosarcoma cell metastasis by suppressing miR-149-5p synthesis - Huey-En Tzeng (Nature Publishing Group, 2021)
Abstract Chondrosarcoma is a malignancy of soft tissue and bone that has a high propensity to metastasize to distant organs. Nerve growth factor (NGF) is critical for neuronal cell growth, apoptosis, and differentiation, and also appears to promote the progression and metastasis of several different types of tumors, although the effects of NGF upon chondrosarcoma mechanisms are not very clear. We report that NGF facilitates lysyl oxidase (LOX)-dependent cellular migration and invasion in human chondrosarcoma cells, and that NGF overexpression enhances lung metastasis in a mouse model of chondrosarcoma. NGF-induced stimulation of LOX production and cell motility occurs through the inhibition of miR-149-5p expression, which was reversed by PI3K, Akt, and mTOR inhibitors and their respective short interfering RNAs. Notably, levels of NGF and LOX expression correlated with tumor stage in human chondrosarcoma samples. Thus, NGF appears to be a worthwhile therapeutic target for metastatic chondrosarcoma.